Heparin dose during percutaneous coronary intervention: how low dare we go?. Issue 4 (1st October 2002) - Niccoli, G; Banning, A P
Abstract : Despite dramatic advances in percutaneous coronary intervention, including coronary stents and potent antiplatelet agents, unfractionated heparin remains the standard procedural anticoagulant. Tradition and habit may have considerable influence over dose selection. A review of the role and dosage of heparin during PCI appears to be overdue